Mechanical and Microstructural Performances of One-Part Alkali-Activated Fly Ash Mortars with Thermally Activated Palm Oil Decanter Cake - Chan, Yoon Tung; Shukor Lim, Nor Hasanah Abdul; Ishak, Shafiq; Samadi, Mostafa; Ngian, Shek Poi; Kek, Hong Yee; Tan, Shea Qin (Journal of Composites and Biodegradable Polymers, 2025)
The utilisation of waste-derived precursors in one-part alkali-activated materials offers a promising route towards more sustainable cementitious systems. This study evaluates calcined palm oil decanter cake (PODC) as a partial replacement for Class C fly ash in one-part alkali-activated mortars. PODC was thermally treated at 400 °C to reduce organic content while retaining biochar and incorporated at replacement levels of 5–20%. Fresh properties, physical characteristics, mechanical performance, and microstructural development were systematically assessed. Increasing PODC content reduced flowability and shortened setting time, attributed to the lower density, irregular particle morphology, and water-retention behaviour of biochar. Despite these changes, bulk density, water absorption, and apparent porosity were only marginally affected, indicating that matrix compactness was largely preserved. Strength development depended strongly on replacement level. Mortars with 10% and 15% PODC showed improved performance relative to the control, with 15% achieving the highest long-term compressive strength due to additional reactive Ca, K, and Si contributed by PODC. The 10% replacement provided a more balanced response, combining improved workability, stable early-age strength, and enhanced flexural and splitting tensile strengths. In contrast, 20% replacement led to strength reduction associated with increased porosity and a weaker interfacial transition zone. XRD, TG–DTA, and SEM–EDS confirmed substantial consumption of PODC phases and the formation of well-developed binding gels (C–S–H, C–A–S–H, and alkali-substituted (N,K)–A–S–H). Residual biochar acted as a preferential site for gel nucleation, promoting matrix cohesion. Overall, calcined PODC is an effective supplementary precursor for one-part fly ash-based alkaline-activated mortars, with an optimal replacement range of 10–15%.